303 LISTERIA MONOCYTOGENES INFECTION OF PERIPHERAL TISSUES TRIGGERS MONOCYTE ENTRY AND GENE EXPRESSION IN THE BRAINS OF EXPERIMENTALLY INFECTED MICE. (1st January 2005) - Drevets, D. A.; Dillon, M. J.; Schawang, J. S.; Lerner, M.; Bronze, M. S.; Brackett, D. J.
Abstract : Purpose: Recent data show that the Ly-6Chi monocyte subpopulation transports intracellular Listeria monocytogenes (Lm) into the brains of systemically infected mice. However, it is not clear whether peripheral or CNS infection triggers these monocytes to enter the brain. These experiments sought to establish whether entry of Ly-6Chi monocytes into the brain required bacterial infection of that organ, and determine the extent to which systemic Lm infection altered global gene expression in the brain. Methods: C57BL/6 mice were infected i.v. with wild type (WT) Lm, or with ΔactA or Δhly Lm mutants that can (ΔactA) or cannot (Δhly) replicate intracellularly. The mice were euthanized, exsanguinated, and perfused. The brain was removed and analyzed for bacterial infection, monocyte influx, or gene expression. Lm infection was established by quantitative culture. Numbers of Ly-6Chi monocytes were measured by FACS analysis. Gene expression was measured using the BD Atlas 5K gene array and by real-time PCR. Cytokine concentrations in the serum were quantified using ELISA and cytometric bead array. Statistical and data analyses were performed with the Student's t-test and GeneSpring 5.0 software. Results: Systemic infection with 105 CFU WT Lm and 107 CFU ΔactA Lm mutants induced a significant influx of Ly-6Chi monocytes into the brain concomitant with significant upregulation of MCP-1 gene expression in that organ. In contrast, infection with 107 CFU Δhly Lm mutants induced neither response. Kinetic analyses of gene expression in the brain and microbiological studies of WT Lm-infected mice demonstrated widespread gene upregulation at days 1 and 2 post-infection, even though the brains were sterile. Serum levels of IFN-γ, TNF-α, and IL-6 were significantly increased from day 1 post-infection. Conclusions: Initial recruitment of Ly-6Chi monocytes into the brain does not require brain infection and is not a generic response to systemic bacterial infection. However, it is necessary that infecting bacteria escape from phagosomes and replicate intracellularly. In addition to upregulation of MCP-1 gene expression, there is widespread gene upregulation in the brain before bacteria enter that organ. These data suggest that pro-inflammatory cytokines produced by the innate immune response to intracellular replication of Lm in peripheral organs modulate gene expression in the CNS, a key consequence of which is recruitment of Ly-6Chi monocytes, some of which also contain intracellular bacteria, into the brain.